Synaptic potentiation and rapid antidepressant response to ketamine in treatment-resistant major depression: A replication study. (30th January 2019) - Nugent, Allison C.; Wills, Kathleen E.; Gilbert, Jessica R.; Zarate, Carlos A.
Highlights: Healthy and depressed subjects received tactile stimulation during MEG recording. Subjects went on to receive infusions of 0.5mg/kg IV ketamine and placebo. MEG recordings were repeated after both infusions. Only patients who responded to ketamine demonstrated synaptic potentiation. The study replicates earlier findings that ketamine may induce plasticity. Abstract: Preclinical and clinical evidence has demonstrated that ketamine has rapid antidepressant effects. Studies using pre-treatment with an AMPA inhibitor suggest that enhancing AMPA throughput is crucial to ketamine's effects, including increases in both basal and evoked gamma power. This study sought to replicate previous findings of increased gamma response to a somatosensory stimulus at 230 min and Day 1 in ketamine responders versus non-responders in 31 depressed subjects and 25 healthy controls. A significant difference in peak gamma power was seen in the depressed ketamine responders versus non-responders. These results implicate AMPA throughput in ketamine's mechanism of antidepressant action.